The Direction of Indonesia’s Legal Policy on the ASEAN Mutual Legal Assistance Treaty in Criminal Matters: A Path to Law Reform in Cross-Border Crime Enforcement in Southeast Asia - Ridwan Arifin; Rodiyah Rodiyah; Waspiah Waspiah; Asyaffa Ridzqi Amandha; Elizabeth Yunita Krisnawati; Tirta Sandi; Michael Timothy Napitupulu (Journal of Law and Legal Reform, 2024)
This research explores Indonesia’s legal policy on the ASEAN Mutual Legal Assistance Treaty in Criminal Matters (AMLAT) and its implications for law reform in the enforcement of cross-border crime in Southeast Asia. AMLAT plays a critical role in facilitating legal cooperation among ASEAN member states in criminal matters, addressing challenges posed by transnational crimes such as human trafficking, drug smuggling, and cybercrime. Despite its significance, Indonesia faces legal and procedural gaps in aligning its domestic legal framework with AMLAT provisions, creating obstacles in efficient criminal law enforcement across borders. The novelty of this study lies in its focus on Indonesia’s unique legal challenges and reform needs in the context of AMLAT, an area that has received limited scholarly attention. While previous studies have explored AMLAT’s role at a regional level, this research specifically investigates the legal and policy issues within Indonesia and how they affect broader ASEAN cooperation on cross-border crime. The urgency of this research is underscored by the increasing prevalence of transnational crimes in Southeast Asia, exacerbated by advancements in technology and globalization. A more robust legal framework is crucial for Indonesia to effectively collaborate with ASEAN members in combating these crimes. The contribution of this study is twofold. First, it provides a comprehensive analysis of the current state of Indonesia’s legal policy on AMLAT, highlighting key areas for legal reform. Second, it offers practical recommendations for policymakers to strengthen Indonesia’s role in regional legal cooperation, ensuring more effective cross-border crime enforcement in Southeast Asia.